History of Indian Air Defence Artillery 1940-1945 - Singh, Mandeep (Brill | Manohar Publishers & Distributors, 2022)
In 1921, the eighth Anti-Aircraft Battery of Royal Artillery was first stationed in India. However, it was only after two decades that the threat from the Japanese expansionism made India to finally realise how ill-prepared its anti-aircraft defences were. Starting from a Battery raised at Colaba, Indian Anti-Aircraft Artillery soon expanded to over thirty-four regiments for India to have the second largest concentration of Anti-Aircraft defences outside the Great Britain. At one time, India had more Anti-Aircraft Regiments than that of field artillery. Numbers aside, Indian Anti-Aircraft gunners served in varied battlefields with honour, both during defeat and victory. If they were at Singapore as the fortress fell, they kept the Japanese Air Force at bay when Allied forces retreated from Burma, and later formed part of the vanguard when the Allies returned to Burma in triumph. Indian Anti-Aircraft Regiments served in Singapore, Malaya, Burma, Maldives, Aden and Iraq. They were truly representative as all regiments comprised of varied races and castes. It had a separate training centre for women and was one of the first to enlist women when the WAC(I) manned its operation rooms and drove lorries. They defended key installations, protected cities, served with field formations, participated in amphibious operations, served at remote locations facing odds and administrative apathies.